2014
DOI: 10.1371/journal.pone.0098515
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2 Is Amplified in the NCI-H716 Colorectal Cancer Cell Line and Is Required for Growth and Survival

Abstract: Aberrant kinase activation resulting from mutation, amplification, or translocation can drive growth and survival in a subset of human cancer. FGFR2 is amplified in breast and gastric cancer, and we report here the first characterization of FGFR2 gene amplification in colorectal cancer in the NCI-H716 colorectal cancer cell line. FGFR2 is highly expressed and activated in NCI-H716 cells, and FGFR selective small molecule inhibitors or FGFR2 shRNA strongly inhibited cell viability in vitro, indicating “addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 27 publications
4
38
0
Order By: Relevance
“…In some instances (FGFR2, ALK or NTRK1), overexpression of the TK gene was associated with amplification or translocation of the corresponding locus. The same genetic alterations have been previously reported in CRC cells and patients [26][27][28] , thus validating our approach. Our data further suggest that overexpression of TK sustains primary resistance to EGFR blockade, and could be used to identify patients unlikely to respond to cetuximab or panitumumab.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In some instances (FGFR2, ALK or NTRK1), overexpression of the TK gene was associated with amplification or translocation of the corresponding locus. The same genetic alterations have been previously reported in CRC cells and patients [26][27][28] , thus validating our approach. Our data further suggest that overexpression of TK sustains primary resistance to EGFR blockade, and could be used to identify patients unlikely to respond to cetuximab or panitumumab.…”
Section: Discussionsupporting
confidence: 86%
“…We decided to focus on TKs for which targeted agents are in clinical trial or are already approved for treatment, namely ALK, FGFR2, KIT, NTRK1, NTRK2, RET and PDGFRA. This analysis revealed that the overexpression of NTRK1 and FGFR2 is associated to molecular alterations, such as gene translocation (NTRK1) or gene amplification (FGFR2; Supplementary Figs 5 and 6), previously described in cellular models and in cancer patients [26][27][28] , thus validating the experimental approach. The other TK outlier genes were not previously reported in CRC cells.…”
Section: Resultssupporting
confidence: 71%
“…FGFR-1 and FGFR-2 were over-expressed in NCI-H716 cells [15], but were undetected in HT-29 cells (Fig. 1a).…”
Section: Resultsmentioning
confidence: 95%
“…Katoh and Nakagama (27) demonstrated that the expression of FGFR2 was amplified in breast and gastric cancer. In the colorectal cancer NCI-H716 cell line, which exhibits a high expression of FGFR2, the inhibition of FGFR2 by small molecule inhibitors or FGFR2 short hairpin (sh)RNA was shown to decrease cell viability (28). In pancreatic cancer, tumor cells with FGFR2-shRNA transfection exhibited attenuated proliferation rates, migration and invasion levels, and a reduced level of phosphorylation of ERK compared with that of the control cells (29).…”
Section: Discussionmentioning
confidence: 99%